2015
DOI: 10.1016/j.biopsycho.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A time to be stressed? Time perspectives and cortisol dynamics among healthy adults

Abstract: Perceptions of past, present, and future events may be related to stress pathophysiology. We assessed whether Time Perspective (TP) is associated with cortisol dynamics among healthy adults (N = 61, Ages = 18–35, M = 22.9, SD = 4.1) exposed to the Trier Social Stress Test (TSST). TP was measured according to two profiles: maladaptive Deviation from Balanced TP (DBTP) and adaptive Deviation from Negative TP (DNTP). Eight salivary cortisol samples were analyzed using area under the curve with respect to ground (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 118 publications
(140 reference statements)
2
28
0
1
Order By: Relevance
“…It has also been reported that higher BTP is associated with higher life satisfaction and general happiness (Barsics, Rebetez, Rochat, D'Argembeau, & Van der Linden, 2017;Boniwell & Zimbardo, 2004;Simons, Peeters, Janssens, Lataster, & Jacobs, 2016;Webster & Ma, 2013;Gao, 2011), extraversion (Stolarski, 2016;, positive orientation (Sobol-Kwapińska & Jankowski, 2016), satisfaction with interpersonal relations (Stolarski, Wojtkowska, & Kwiecińska, 2016), emotional intelligence (Stolarski, Bitner, & Zimbardo, 2011), and mindfulness (Selma & Sircova, 2013;Stolarski, Wojtkowska, & Kwiecińska, 2016). Moreover, higher BTP is negatively correlated with pathophysiological stress (Olivera-Figueroa, Juster, Morin-Major, Marin, & Lupien, 2015). A more balanced profile of time perspective is related to fluid intelligence and higher executive control, which means that cognitive abilities play an important role in accepting time balance (Zajenkowski, Stolarski, Witowska, Maciantowicz, & Łowicki, 2016).…”
Section: Balanced Time Perspectivementioning
confidence: 95%
“…It has also been reported that higher BTP is associated with higher life satisfaction and general happiness (Barsics, Rebetez, Rochat, D'Argembeau, & Van der Linden, 2017;Boniwell & Zimbardo, 2004;Simons, Peeters, Janssens, Lataster, & Jacobs, 2016;Webster & Ma, 2013;Gao, 2011), extraversion (Stolarski, 2016;, positive orientation (Sobol-Kwapińska & Jankowski, 2016), satisfaction with interpersonal relations (Stolarski, Wojtkowska, & Kwiecińska, 2016), emotional intelligence (Stolarski, Bitner, & Zimbardo, 2011), and mindfulness (Selma & Sircova, 2013;Stolarski, Wojtkowska, & Kwiecińska, 2016). Moreover, higher BTP is negatively correlated with pathophysiological stress (Olivera-Figueroa, Juster, Morin-Major, Marin, & Lupien, 2015). A more balanced profile of time perspective is related to fluid intelligence and higher executive control, which means that cognitive abilities play an important role in accepting time balance (Zajenkowski, Stolarski, Witowska, Maciantowicz, & Łowicki, 2016).…”
Section: Balanced Time Perspectivementioning
confidence: 95%
“…We focus on the salivary cortisol mainly for the consideration of practice applications. Salivary cortisol is more readily available than urine specimens, and is more convenient to collect at home for large scale epidemiological studies [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These time perspectives are found to be associated with several behavioural and psychological domains; for example, Diaz-Morales et al (2007) report that low future orientation is associated with procrastination and indecision, Zimbardo, Keough, and Boyd (1997) report that present orientation is associated with risky driving, and Sailer et al (2014) report that lower past negative and present fatalistic scores, coupled with higher present hedonistic scores, were associated with greater life satisfaction. Deviation from a balanced time perspective (Stolarski et al, 2011), describing the fit between an individual's TP and an optimal balance between past, present and future orientation, has previously been shown to be associated with poorer subjective well-being (Zhang, Howell, & Stolarski, 2013), negative mood states (Stolarski, Matthews, Postek, Zimbardo, & Bitner, 2014), and lower systemic cortisol production (Olivera-Figueroa, Juster, Morin-Major, Marin, & Lupien, 2015).…”
Section: Introductionmentioning
confidence: 99%